THE EFFECT OF FINANCIAL RATIO FACTORS ON THE PERCENTAGE OF INCOME INCREASING OF AUTOMOTIVE COMPANIES IN INDONESIA - Mohammad Nugraha, Nugi; Mawarnie Puspitasari, Devy; Amalia, Shendy (International Journal of Psychosocial Rehabilitation, 2020)
Growth profit is a ratio shown by the addition of the company's net profit every year. An increase in the ratio of growth profit will make the company's performance better. The purpose of this study in order to analyze the effect of financial ratio factors shown by Current Ratio, Total Assets Turnover, Net Profit Margin and Return On Assets to the percentage increase in profits of automotive and component sub sector companies. The sampling method using purposive sampling so that 8 companies were selected. The analysis technique is by applying the multiple regression model, coefficient of determination, F test and t test. Based on the proof of the results of this experiment, it is known that all independent variables simultaneously have a significant influence on the volatility of the company's profit increase. Likewise partially, each independent variable has a positive influence on the rate of increase in earnings. The adjusted R square value of 88% indicates that the rate of increase in profit can be explained by independent variables: Current Ratio, Total Assets Turnover, Net Profit Margin and Return On Assets, while the remaining 12% is explained by other variables outside this study.